MELANOMA? LOOK CLOSER - Mota, F. (2015)
Pigmented skin lesions are sometimes misdiagnosed due to clinical similarities between melanocytic and non-melanocytic lesions. We report the case of a patient with a pigmented lesion that clinically resembles melanoma. With dermoscopy, observed features, namely leaf-like areas, allowed us to make the diagnosis of pigmented basal cell carcinoma. This case represents a clinical setting in which clinical examination alone could lead to a misdiagnosis, but with the use of dermoscopy an accurate diagnosis was possible.